Assessing West Java Supply Chain Financing System (SCFS) Using SWOT Analysis - Daud Fahmi Adhim; Nur Budi Mulyono (Politeknik Negeri Bandung, 2023)
Supply chain system implementation consists of two necessary elements, the network design and the information technology (IT). In West Java, Supply Chain Center (SCC) implementation notion is based on the province’s current SMEs circumstances, including low financial performance, decentralized data, and no roadmap between actors. This research analyzes West Java Supply Chain Financing System (SCFS) using strengths, weaknesses, opportunities, and threats (SWOT) analysis. Qualitative methodology was employed for this research. First, the primary data was collected from focus group discussion (FGD) and the secondary data was obtained from West Java government documents. Second, this research used SWOT analysis from collected data which generate nine alternative strategies to build effective SCFS to cope with identified issues and its implications to expand rural financial services, supply chains, and overall sustainable development.